2020
DOI: 10.5433/1679-0359.2020v41n5supl1p1923
|View full text |Cite
|
Sign up to set email alerts
|

Metamitron in the chemical thinning of ‘PS 10711’ peach trees

Abstract: Chemical thinning of fruits may be an alternative practice to hand thinning. Hand thinning must be performed in a short time during the fruiting stage, but lack of manpower and the onerous costs of the operation make it increasingly difficult to employ it at the right time and at the ideal intensity. The objective of this study was to examine the effect of different concentrations of metamitron as a chemical thinner on ‘PS 10711’ peach trees. The experiment was carried out during two harvests in an orchard in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…In the case of cultivar Sensação, in 2015, the application of metamitron resulted in a higher fruit abscission than manual thinning, but, in 2016, the obtained values were similar. Farias et al (2020a) verified that concentrations of metamitron from 100 to 200 mg L -1 applied to 'PS 10711' peach trees caused a lower decrease in fruit, compared with manual thinning. Therefore, the recommended concentration of metamitron is one that ensures a fruit load that is consistent with the fruit set and abscission obtained by manual thinning, leading to a strategically safer and easier practice.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In the case of cultivar Sensação, in 2015, the application of metamitron resulted in a higher fruit abscission than manual thinning, but, in 2016, the obtained values were similar. Farias et al (2020a) verified that concentrations of metamitron from 100 to 200 mg L -1 applied to 'PS 10711' peach trees caused a lower decrease in fruit, compared with manual thinning. Therefore, the recommended concentration of metamitron is one that ensures a fruit load that is consistent with the fruit set and abscission obtained by manual thinning, leading to a strategically safer and easier practice.…”
Section: Resultsmentioning
confidence: 69%
“…The authors also found that negative effects of high temperatures on blooming were higher in the case of 'Granada' than in that of 'Maciel'. Likewise, Farias et al (2020aFarias et al ( , 2020b reported differences among cultivars due to chemical thinning. These results reinforce the hypothesis that the efficiency of a chemical thinning agent in peach abscission depends on the environmental conditions of the cultivation area and that further studies are fundamental to characterize the effects of this treatment on different cultivars and stages of fruit development.…”
Section: Resultsmentioning
confidence: 99%
“…Os frutos das plantas que receberam raleio mais intenso apresentam média de 93 g, enquanto os das plantas sem raleio, apenas 50 g (Figura 1). Com a mesma cultivar, em Eldorado do Sul-RS, também foi observada redução da produção por planta com o raleio manual ou químico, e aumento da massa média dos frutos, atingindo 97,87 g e 110,77 g com o raleio manual, nas safras de 2016 e 2017, respectivamente (Farias et al, 2020). Estes valores foram próximos aos obtidos neste trabalho, apesar da diferença na densidade de plantio, que foi de 727 plantas ha -1 no experimento destes autores e de 416 plantas ha -1 no presente trabalho.…”
Section: Resultsunclassified
“…O raleio mecânico pode ser realizado nas flores com equipamentos de vibração, reduzindo o tempo para a realização desta prática e realizando de forma antecipada à formação dos frutos (Simões et al, 2013;Barreto et al, 2019). O raleio químico consiste na aplicação de produtos químicos que inibem a formação de gemas floríferas, que causam toxidez à flor, ou que induzem a abscisão de flores ou frutos (Pavanello & Ayub, 2012;Giovanaz et al, 2016b;Gabardo et al, 2019;Farias et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation